ANTE PAVELIC: CASE STUDY OF CULTUROPATHY AND SOCIOPATHIES OF IDENTITY(VISUAL-ANALYTICAL PORTRAIT). PART 1 (Вісник: Міжнародні відносини, 2024)
The purpose of the article is a visual-analytical portrayal of the personality of Ante Pavelić in the context of the cultural and socio-systemological theory of cultural pathologies and sociopathies of identity. As a result of the study, it was concluded that Pavelić's ethnopolitics, genocidal rhetoric towards the Serbs, as well as the encouraged practices of serbicide reveal a pronounced despotism, necrophilia, a steady predominance of affects of destructive hatred and envy towards ethnic competitors, as well as his real attitude towards the Ustaše, left to the mercy of fate by him to be torn to pieces by the communists while fleeing from Croatia with all the loot, reveals his significant moral defectiveness, as well as gives reason to interpret it as a derivative of the corresponding cultural pathologies and sociopathies of identity.
Keywords: identity, cultural and social systemology, visual analytics, sociology of international relations, identity cultural pathologies, identity sociopathies